2006
DOI: 10.1099/mic.0.28620-0
|View full text |Cite
|
Sign up to set email alerts
|

The phylogeny of Staphylococcus aureus – which genes make the best intra-species markers?

Abstract: The ability to make informed decisions on the suitability of alternative marker loci is central for population and epidemiological investigations. This issue was addressed using Staphylococcus aureus as a model population by generating nucleotide sequence data from 33 gene fragments in a representative sample of 30 strains. Supplementing the data with pre-existing multilocus sequence typing data, an intra-species tree based on~17?8 kb of sequence was reconstructed and the goodness of fit of each individual gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
54
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 41 publications
11
54
0
1
Order By: Relevance
“…These results confirmed that the improved MLST scheme has a better discriminatory ability than the previous ones and should be adopted henceforth as the unique and universal S. epidermidis MLST scheme (4).…”
Section: Discussionsupporting
confidence: 76%
“…These results confirmed that the improved MLST scheme has a better discriminatory ability than the previous ones and should be adopted henceforth as the unique and universal S. epidermidis MLST scheme (4).…”
Section: Discussionsupporting
confidence: 76%
“…In other words, strains within our sample of the population in one square metre of soil can be more diverged from each other in these replicons than from a strain originating 41600 km away in very different climatic conditions. It is usual that genes of accessory or unknown function, which are frequent on extrachromosomal replicons, are more polymorphic than core genes that may be under strong purifying selection (for example, Cooper and Feil (2006)), but it is interesting to observe that this polymorphism extends to local populations and not just wider strain collections. Of course, we are looking here at nucleotide divergence of genes that are shared by all strains, rather than at the presence or absence of potentially adaptive accessory genes, which are discussed in the next section.…”
Section: Discussionmentioning
confidence: 99%
“…adhesion genes) are at least as informative for phylogenetic reconstruction as the more slowly evolving housekeeping genes (e.g. MLST) [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%